Bimetallic Cobalt‐Based Phosphide Zeolitic Imidazolate Framework: CoPx Phase‐Dependent Electrical Conductivity and Hydrogen Atom Adsorption Energy for Efficient Overall Water Splitting - Song, Junhua; Zhu, Chengzhou; Xu, Bo Z.; Fu, Shaofang; Engelhard, Mark H.; Ye, Ranfeng; Du, Dan; Beckman, Scott P.; Lin, Yuehe (Advanced energy materials, 2017)
Cobalt‐based bimetallic phosphide encapsulated in carbonized zeolitic imadazolate frameworks has been successfully synthesized and showed excellent activities toward both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Density functional theory calculation and electrochemical measurements reveal that the electrical conductivity and electrochemical activity are closely associated with the Co2P/CoP mixed phase behaviors upon Cu metal doping. This relationship is found to be the decisive factor for enhanced electrocatalytic performance. Moreover, the precise control of Cu content in Co‐host lattice effectively alters the Gibbs free energy for H* adsorption, which is favorable for facilitating reaction kinetics. Impressively, an optimized performance has been achieved with mild Cu doping in Cu0.3Co2.7P/nitrogen‐doped carbon (NC) which exhibits an ultralow overpotential of 0.19 V at 10 mA cm–2 and satisfying stability for OER. Cu0.3Co2.7P/NC also shows excellent HER activity, affording a current density of 10 mA cm–2 at a low overpotential of 0.22 V. In addition, a homemade electrolyzer with Cu0.3Co2.7P/NC paired electrodes shows 60% larger current density than Pt/RuO2 couple at 1.74 V, along with negligible catalytic deactivation after 50 h operation. The manipulation of electronic structure by controlled incorporation of second metal sheds light on understanding and synthesizing bimetallic transition metal phosphides for electrolysis‐based energy conversion. Mixed CoPx phase behavior of copper‐doped cobalt phosphide within zeolitic imidazolate framework catalysts presents extraordinary water‐splitting capability. Theoretical calculation reveals that a much lower free energy of hydrogen adsorption and less covalently bonded atoms upon copper doping are the decisive origins of enhanced catalytic activity.